Short- and medium-term coastal abrasion and accretion rate analysis using GIS in Karawang, West Java - Fauzie, Azis Kemal (Badan Penelitian dan Pengembangan Daerah (BP2D) Provinsi Jawa Barat, 2017)
A GIS-based study using MapInfo software has been performed to examine the short- and medium-term effect of coastal erosion in Karawang, West Java. Assessment of short-term period shows different trends in the consecutive of nine-year data. The balanced trend was found in the first period when abrasion and accretion have the same rate of 12 ha/yr. In second period accretion has dominated by causing emerging land around 27 ha/yr, but erosion only displaced 2 ha/yr of coastal area. In the third period more abrasion process has occurred that made about 15 ha/yr shoreland disappear, but accretion took only 8 ha/yr. Medium-term study using 27-year data confirms more accurate estimation of abrasion and accretion rates. The data suggests that abrasion had affected on area loss more than 15 ha/yr, while accretion gave additional land about double than that. A brief schematic design has been provided in the study as alternative option to minimize the future impacts of coastal erosion by incorporating natural and artificial measures.